Proporciones de aserrín de madera y humus de lombríz y su efecto en el crecimiento de plantones de Carica papaya L. Sinta F1 en vivero, Zungarococha – Perú.2021 - Mori Salinas, Lisbeth del Carmen (2022)
The research work was carried out at the National University of the Peruvian Amazon in the Faculty of Agronomy in the Cattle Project in the Fundo de Zungarococha, entitled "PROPORTIONS OF HUMUS AND SAWDUST IN THE GROWTH OF PLANTS OF Carica papaya L. SINTA F1 IN NURSERY IN ZUNGAROCOCHA - PERU 2021”. The evaluations were carried out 90 days after the research work began, with plots of 1 m x 1 m (1 m2) and an experimental area of 91 m2. With a Complete Random Design (DCA), with three treatments and six repetitions, the treatments under study were: T0 (Control 100% earthworm humus), T1 (90% humus + 10% sawdust), T2 (80% humus + 20% sawdust), T3 (70% humus + 30% sawdust) obtaining the following results: With the treatments T0 (Control 100% earthworm humus) and T1 (90% humus + 10% sawdust) it was possible to increase the height yields of plant (cm), number of leaves/plant, diameter of the crown of the plant (cm), basal diameter of the stem (cm), weight of the whole plant (g), weight of the root (g) and root length (cm ). In this sense, it was shown that at least one of the proportions of humus and sawdust influenced plant height, number of leaves/plants, basal stem diameter, and crown diameter in Zungarococha. According to what was found in this work, the dose of 90% humus + 10% sawdust positively influences the investigation.